Clinicopathological Findings in Pediatric Tubulointerstitial Nephritis: Iranian Experience - Koochak, Aghigh; Babaheidarian, Pegah; Hooman, Nakysa; Mehrazma, Mitra (Journal of Pediatric Nephrology, 2015)
Introduction: Tubulointerstitial disorders are characterized by diseases that affect the vascular and interstitial compartments of the kidney with relative sparing of the glomeruli. They might be either acute or chronic. Acute tubulointerstitial nephritis (TIN) is associated with acute renal failure due to either acute infection of the kidneys or reaction to medication. Chronicinterstitial nephritis is characterized by many syndromes of renal tubular dysfunction that may be primary or secondary due to renal tubular damage from a wide variety of causes. The aim of this study was to evaluate the pathologic characteristics of acute and chronic TIN and their probable causes. Materials and Methods: All native kidney biopsy specimens with a diagnosis of tubulointerstitial nephritis admitted to Ali-Asghar Hospital, a pediatric referral center in Tehran, from 1983 to 2013 were retrospectively re-evaluated. The demographic data of the patients were collected and pathologic findings were reviewed. Results: Forty-four patients, 18 males and 26 females with a mean age of 8.8 years (SD=4), were enrolled in this study. Thirty-seven (84%) patients had chronic and 7 (16%) had acute TIN. The disease was primary in 32 (72%) patients with a diagnosis of familial nephronophthisis and medullary cystic disease and 12 (28%) had other diseases. Kidney biopsy showed similar pathologic findings including periglomerular fibrosis (72%), different scores of interstitial fibrosis/tubular atrophy (91%), infiltration of inflammatory cells, and segmental and global glomerular sclerosis (89%). Conclusions: Acute and chronic tubulointerstitial nephritis with different etiologies has similar pathologic findings. The patients mostly present in the late stages of the disease; therefore, determining the etiology is impossible. Many cases are congenital. Keywords: Nephritis, Interstitial, Child, Renal Insufficiency.